2015
DOI: 10.4103/0019-509x.178383
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of buccal mucosa: A site specific clinical audit

Abstract: The strong influence of overall disease stage, tumor size, nodal status, final histopathological report and habits of tobacco/betel quid chewing, on prognosis; emphasizes the importance of early diagnosis and prevention of carcinoma of buccal mucosa in the Indian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 1 publication
8
14
1
Order By: Relevance
“…These findings concur with earlier reports on site predilection whereby tongue was the most common site in communities with high prevalence of smoking (Gorsky et al, 2004), whereas chewing is associated with tumours of the buccal mucosa (Singhania, Jayade, Anehosur, Gopalkrishnan, & Kumar, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings concur with earlier reports on site predilection whereby tongue was the most common site in communities with high prevalence of smoking (Gorsky et al, 2004), whereas chewing is associated with tumours of the buccal mucosa (Singhania, Jayade, Anehosur, Gopalkrishnan, & Kumar, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Almost two‐thirds of the tumours among the Chinese occurred at the tongue, which is in accordance with their affinity towards the habit of concurrently smoking and drinking whereas more than half of the Indians and Indigenous people were diagnosed with cancer of the buccal mucosa, which can be attributed to the high prevalence of BQ chewing in these ethnic groups. These findings concur with earlier reports on site predilection whereby tongue was the most common site in communities with high prevalence of smoking (Gorsky et al, ), whereas chewing is associated with tumours of the buccal mucosa (Singhania, Jayade, Anehosur, Gopalkrishnan, & Kumar, ).…”
Section: Discussionsupporting
confidence: 92%
“…The median age of our patients was 52 years (range 24–85), which is similar to age distribution reported by other studies from India. [ 7 8 ] This validates the fact that prolonged contact of the quid with the mucosal site is suggested as an important etiological factor in terms of high incidence at specific sites and high frequency and longer duration of habit among older individuals. [ 7 9 ] Out of the 409 patients, only 29.1% were females.…”
Section: Discussionsupporting
confidence: 67%
“…26 Sighania V et al reported in their study major bulk of the cases presented to them were in stage IV (72%) while minimum presentation was that of stage I patients. 27 In our study it was noticed that only 30% of cases presented in stage I and II while 70% presented in stage III and IV.…”
Section: Staging Of Malignancymentioning
confidence: 48%